Pengaruh Penerapan RNAV 1 Medan East TMA Terhadap Kelancaran Lalu Lintas Penerbangan Di Perum LPPNPI Kantor Cabang Medan - Winkki Sevtia; Lina Rosmayanti; Yanuar Jinu Satiti; Elvi Amir (Politeknik Penerbangan Indonesia Curug, 2021)
This study aims to determine the effect RNAV-1 Medan East TMA implementation of air traffic flow in Medan Branch Office Airnav Indonesia. The research was conducted at the Medan Approach Control Unit from January to March 2020. The method used is quantitative, the data collection technique uses a Likert scale questionnaire, the data analysis technique is Product Moment Correlation, the coefficient of determination and regression. The population was 23 Air Traffic Controller. The study concludes that there is a strong positive relationship between the application of RNAV-1 to the Smoothness of Aviation Traffic during peak hours with a correlation coefficient of 0.737 and a coefficient of determination of 54.4%, meaning that the effect of implementing RNAV-1 on Smooth Air Traffic and the rest is determined by another factors.